Synthesis of Bodipy-Tagged Galactoconjugates and Evaluation of Their Antibacterial Properties - Chiara Maria Antonietta Gangemi; Maura Monforte; Antonino Arrigo; Paola Maria Bonaccorsi; Sabrina Conoci; Antonella Iaconis; Fausto Puntoriero; Domenico Franco; Anna Barattucci (Molecules, 2024)
As a development of our research on biocompatible glycoconjugate probes and specifically multi-chromophoric systems, herein, we report the synthesis and early bactericidal tests of two luminescent glycoconjugates whose basic structure is characterized by two boron dipyrromethene difluoride (BODIPY) moieties and three galactoside rings mounted on an oligophenylene ethynylene (OPE) skeleton. BODIPY fluorophores have found widespread application in many branches of biology in the last few decades. In particular, molecular platforms showing two different BODIPY groups have unique photophysical behavior useful in fluorescence imaging. Construction of the complex architecture of the new probes is accomplished through a convergent route that exploits a series of copper-free Heck–Cassar–Sonogashira cross-couplings. The great emergency due to the proliferation of bacterial infections, in conjunction with growing antibiotic resistance, requires the production of new multifunctional drugs and efficient methods for their targeted delivery to control bacteria-associated diseases. Preliminary studies of the glycoconjugate properties as antibacterial agents against representatives of Gram-negative (P. aeruginosa) and Gram-positive (S. aureus) pathogens, which are associated with chronic infections, indicated significant bactericidal activity ascribable to their structural features.